Bacteriological Quality Testing MPN Coliform Enterobacteriae On Soy Milk Sold At The Youtefa Market In 2023 - Bakti Kurniawan, Fajar (Jurnal EduHealth, 2024)
Soybeans are a source of high quality vegetable protein for human consumption or made into products including soy milk. Poorly processed soy milk can be contaminated with disease-causing bacteria, one of which is the Coliform bacteria group. Coliform bacteria are a group of bacteria that are contained in large quantities in human and animal waste, so these bacteria are often used as indicators of food and water quality. Coliform bacteria can cause various diseases, one of which is diarrhea. The aim of this research is to determine the contamination of Coliform bacteria in unbranded soy milk sold at Youtefa Market. The type of research used is descriptive experimental research. Samples were analyzed using the Most Probable Number (MPN) method. The research results showed that 5 of the 5 samples tested were above the standard value, because the MPN value was >3/ml. The conclusion from the data analysis can be concluded that all samples tested contained Coliform bacteria contamination. Keywords: Coliform, Youtefa Market, Soy Milk.